Distinct impacts of two types of El Niño events on northern winter high-latitude temperatures simulated by CMIP6 climate models - Sangwoo Lee; Hyo-Seok Park; Se-Yong Song; Sang-Wook Yeh (Environmental Research Letters, 2023)
The interannual variability of the Northern Hemisphere winter climate is strongly linked to the El Niño-southern oscillation (ENSO). While North Pacific and North America often exhibit a robust response to ENSO, so-called the Pacific–North America pattern, the Arctic and Eurasian climate responses to ENSO remain elusive. This study examines 40 different climate models from the coupled model intercomparison project phase 6 (CMIP6) to find the distinct Arctic and Eurasian temperature response to two types of El Niño events. Specifically, Central Pacific El Niño events are accompanied by significant pan-Arctic warming, whereas Eastern Pacific (EP) El Niño events are accompanied by cooling over the Barents-Kara Seas and Eurasian continent. During the EP El Niño events, pan-Arctic sea-level pressure (SLP) effectively strengthens, leading to weaker westerlies and surface air cooling over the northern Eurasian continent. These distinct Arctic and Eurasian winter temperature responses to two types of El Niño do not appear clearly in reanalysis data, spanning 1979–2021, probably because of the small sample size of El Niño events since the satellite era.